ANALISI NILAI KARAKTER BERBAKTI KEPADA ORANG TUA DALAM NOVEL IBUK KARYA IWAN SETYAWAN - Suhailasari, Suhailasari; Arfanti, Yulia (Jurnal Bahastra, 2023)
Long prose essay novels tell about human life, the surrounding community and highlight the character and characteristics of each actor. Values give meaning to life, provide reference, starting point and purpose of life. Character is the value of kindness in the form of action or behavior. The purpose of this research is to know the character value of filial piety to parents. The method used in this research is using descriptive qualitative method. Data collection techniques are carried out by reading and understanding the data obtained. The data analysis techniques used are: Reading novels, Describing novels, Analyzing, identifying novels, Taking and compiling conclusions. The data source for this research is the novel Ibuk. This novel will be the author's main study. The results of this study concluded that there were  footage containing aspects of obeying parents,  footage containing aspects of respect, footage containing aspects of lightening the burden on parents, and footage containing aspects of serving parents. Iwan Setyawan conveys many useful character values for readers by bringing the novel's story to life.